FRI0319 A practical simple dose escalation regimen for mild hydroxychloroquine-induced hypersensitivity reaction. (12th June 2018) - Takamasu, E.; Nasa, Y.; Takahashi, H.; Sugii, S.; Yokogawa, N.
Abstract : Background: In a recent Japanese clinical trial of hydroxychloroquine (HCQ), HCQ-induced hypersensitivity reaction occured in 4.9% (5/103) including a case of Stevens-Johnson syndrome. 1 Several desensitisation methods were proposed, however the protocols were very complicated for routine practice. 2 Recently, a simple dose-escalation regimen of sulfamethoxazole-trimethoprim (SMX-TMP) showed better tolerability than standard dosing. 3 Objectives: To investigate the incidence and risk factors of HCQ-induced hypersensitivity and propose a simple dose-escalation regimen for HCQ-induced hypersensitivity. Methods: This is a single-centre, retrospective study. The subjects were Japanese SLE patients who started HCQ between Apr 1, 2009 and June 30, 2017 at Tokyo Metropolitan Tama Medical Centre. HCQ was prescribed with a dosage of 6.5 mg/ideal body weight (IBW) kg or less. We identified the cases of HCQ-induced hypersensitivity by reviewing electronic medical charts and pictures taken by patients or physicians. We diagnosed with HCQ-induced hypersensitivity if generalised eruption occurred within a month of starting HCQ and resolved completely after withdrawal of HCQ. We used the simple dose escalation regimen, starting from 40 mg/day with weekly increments by 40 mg, for patients with HCQ-induced hypersensitivity who did not require hospitalisation or systemic administration of glucocorticoids. We compared the clinical parameters (age, sex, dosage/actual or ideal body weight, starting dose, use of immunosuppresives, use of SMX-TMP, profile of autoantibodies) between patients with HCQ-induced hypersensitivity and those without HCQ-induced hypersensitivity. We also evaluated the success rate of our dose escalation regimen. Results: Total 234 SLE patients were analysed. HCQ-induced hypersensitivity reaction were identified in 20 cases (8.5%). All cases developed mild generalised maculopapular rashes 17 (IQR 7.8–28.8) days after initiation of HCQ. No patient required hospitalisation or systemic glucocorticoid therapy. Among the clinical parameters compared, only anti-Sm antibody was associated with HCQ-induced hypersensitivity (table 1). HCQ was restarted in 10 patients using the simple dose escalation regimen. Among them 9 patients successfully continued HCQ and only one discontinued due to reappearance of mild hypersensitivity reaction. Conclusions: HCQ-induced hypersensitivity reaction typically presents with mild generalised eruption 1–4 weeks after starting HCQ. Restarting HCQ with the simple dose escalation regimen may be a practical option for patients with mild HCQ-induced hypersensitivity reaction. References: [1] Yokogawa N, et al. Effects of Hydroxychloroquine in Patients With Cutaneous Lupus Erythematosus:A Multicenter, Double-Blind, Randomized, Parallel-Group Trial. Arthritis Rheumatol 2017;69:791–799. [2] Tal Y, et al. Hydroxychloroquine desensitization, an effective method to overcome hypersensitivity-a multicenter experience. Lupus2017;1961203317735185. [3] Utsunomiya M, et al. Optimal regimens of sulfamethoxazole-trimethoprim for chemoprophylaxis of Pneumocystis pneumonia in patients with systemic rheumatic diseases: results from a non-blinded, randomized controlled trial. Arthritis Res Ther2017;19:7. Disclosure of Interest: None declared